2020
DOI: 10.1039/c9ra10365a
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 cytoplasmic/nuclear translocation as a new marker of cellular stress. A Caco2 case study

Abstract: Biomarkers of cell stress are important for proper diagnosis, and in studies of how cells respond to drug treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Recent studies suggested that Thymosin β4 (Tβ4), a multifunctional and widely distributed peptide, plays a pivotal role in several physiological and pathological processes in the body, including increasing angiogenesis and proliferation while inhibiting apoptosis and inflammation [ 58 ]. Tβ4 acts as an endogenous iron chelator, influencing anti-oxidative processes related to free iron ions and ROS production, its administration increases the expression of oxidative stress genes [ 58 ], and it could be used as a new and early biomarker of cellular stress [ 59 ]. Tβ4 is expressed in the human intestine and modulates the immune system [ 60 ], and it is believed to be useful in the treatment of gastrointestinal disorders [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that Thymosin β4 (Tβ4), a multifunctional and widely distributed peptide, plays a pivotal role in several physiological and pathological processes in the body, including increasing angiogenesis and proliferation while inhibiting apoptosis and inflammation [ 58 ]. Tβ4 acts as an endogenous iron chelator, influencing anti-oxidative processes related to free iron ions and ROS production, its administration increases the expression of oxidative stress genes [ 58 ], and it could be used as a new and early biomarker of cellular stress [ 59 ]. Tβ4 is expressed in the human intestine and modulates the immune system [ 60 ], and it is believed to be useful in the treatment of gastrointestinal disorders [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…New molecular clinical test are now available [30,31] and new biological approach are able to expand the number of diagnostic strategies [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…At the subcellular level, Tβ4 is localized in the cytoplasm and nucleus, and can translocate between compartments in some conditions [13]. For instance, starvation and other stress conditions alter the expression of Tβ4 in HepG2 cells (2-fold increase of mRNA expression respect to the normal conditions) and lead to peptide translocation from the cytoplasm into the nucleus [36][37][38]. Extracellular Tβ4 is released by cells and found in large amounts in extracellular fluids.…”
Section: Discussionmentioning
confidence: 99%
“…The excised kidneys were cut into small pieces and fixed in a mixture of 3% formaldehyde and 0.1% glutaraldehyde in 0.1 M cacodylate buffer, pH 7.2, then rinsed and stored in 0.1 M cacodylate buffer at 4°C. As described in previous works, [7][8][9] samples were dehydrated in a cold methanol in ascending concentrations and infiltrated with LR gold resin, transferred to gelatin capsules or to flat polyethylene molds filled with fresh resin and placed in polymerization chamber under UV light (365 nm) at −20°C. For light microscopic observations, 1 µ-thick sections stained with toluidine blue were observed and photographed in a Leica 2000 microscope.…”
Section: Methodsmentioning
confidence: 99%